PEMODELAN SISTEM AKTUATOR PNEUMATIK UNTUK PENGENDALIAN FLEKSIBILITAS BODI KENDARAAN - Christof Geraldi Simon; Formanto Paliling; Risa Lasarus; Yusri Anugerah Manapa Ambabunga; Simon Ka'ka; Festo Andre Hardinsi (Badan Penerbit Universitas Muria Kudus, 2026)
This research aims to develop a flexible vehicle body system based on pneumatic actuators to increase the dimensions of limited parking spaces. The methods used include system modeling, electropneumatic control array design, simulation using FluidSIM, and experimental prototype implementation and testing. The control system is designed using a 5/2 directional valve with dual solenoid actuation (Y1 and Y2) that regulates the flow of pressurized air into the pneumatic cylinder to produce a translational motion of the piston that changes the length of the vehicle body linearly Modeling is focused on the relationship between control inputs, actuator response, and structural dimensional changes. Simulations are performed to validate the control logic and response characteristics prior to physical implementation. A length flexibility target of 300 mm is set as a design parameter to meet the parking needs of tight spaces. The test results showed that the system was able to change the length of the vehicle body from 2340 mm to 2040 mm, resulting in a range of flexibility of 300 mm according to the target. These findings show that the proposed method is effective in producing a controlled and applicative adaptive body mechanism, and has the potential to be an engineering solution to improve the efficiency of parking space utilization in land-limited environments.